Applications of Optically Controlled Gold Nanostructures in Biomedical Engineering - Phummirat, Pisrut; Mann, Nicholas; Preece, Daryl (Frontiers in Bioengineering and Biotechnology, 2021)
Since their inception, optical tweezers have proven to be a useful tool for improving human understanding of the microscopic world with wide-ranging applications across science. In recent years, they have found many particularly appealing applications in the field of biomedical engineering which harnesses the knowledge and skills in engineering to tackle problems in biology and medicine. Notably, metallic nanostructures like gold nanoparticles have proven to be an excellent tool for optical tweezers-based micromanipulation due to their large polarizability and relatively low cytotoxicity. In this article, we review the progress made in the application of optically trapped gold nanomaterials to problems in bioengineering. After an introduction to the basic methods of optical trapping, we give an overview of potential applications to bioengineering specifically: nano-bio-materials, cell and molecular engineering, synthetic biology, microfluidics, drug delivery, biosensing, biophotonics and imaging, mechanobiology, and single-molecule biophysics. We highlight the recent research progress, discuss challenges, and provide possible future directions in this field.